Control of Cocoa main pest (Conomorpoha cramerella and Helopeltis spp.) Using Botanical Pesticide and Biological Agents - SISWANTO, .; KARMAWATI, ELNA (Puslitbang Perkebunan, 2012)
One of the causes of cacao low productivity in Indonesia is pests attack on the cacao plantation. There are many types of pests and diseases attacking the cacao trees, however, major pest on cacao plantation in Indonesia include cacao fruit borer (Conopomorpha cramerella) and fruit sucker ladybugs (Helopeltis spp.). To control these pests, farmers generally use chemical insecticides that have negative impacts on the environment. One effort to reduce the negative impacts in pests control is by using botanical pesticides and biological agents, such as parasitoids, predators, and pathogens that are friendly to the environment. The botanical pesticides that can be used to control cacao fruit borer (CFB) and Helopeltis spp. are tobacco, betel forest, neem, yam, anona, gliricidea, jatropha, suren, and tithonia. Entomopathogenic fungi potential to control CFB are B. bassiana, Spicaria sp., Fusarium sp., Verticilium sp., Acrostalagmus sp., Penicillium sp., and Paecilomyces fumosoroseus, while effective fungi to control Helopeltis spp. are B. bassiana and Spicaria sp. This paper describes some aspects related to major cacao pests (such as C. cramerella and Helopeltis spp.) and control effort that is environmentally sound.Keywords: cacao, C. cramerella, Helopeltis spp., botanical pesticides, biological agents